Scintillation balloon for neutrinoless double-beta decay search with liquid scintillator detectors. (16th July 2019) - Obara, S; Gando, Y; Ishidoshiro, K
Abstract: Environmental radioactivity is a dominant background for rare decay search experiments, and it is difficult to completely remove such an impurity from detector vessels. We propose a scintillation balloon as the active vessel of a liquid scintillator in order to identify this undesirable radioactivity. According to our feasibility studies, the scintillation balloon enables the bismuth–polonium sequential decay to be tagged with a 99.7% efficiency, assuming a KamLAND-type (KamLAND = Kamioka Liquid scintillator AntiNeutrino Detector) liquid scintillator detector. This tagging of sequential decay using alpha rays from the polonium improves the sensitivity to neutrinoless double-beta decay while rejecting beta ray background from the bismuth.